Effect of Sorbitol Spraying on Chlorophyl, Total Phenolic and Flavonoid in Fragaria ananassa. Duch. cv. Albion Leaves - Beril Kocaman (Turkish Journal of Agriculture: Food Science and Technology)
Strawberry (Fragaria × ananassa Duch.) is one of the most widely consumed and cultivated fruits worldwide. Sorbitol plays a role in plant responses to many biotic and abiotic stresses. In this research, we intended to understand the effect of sorbitol spraying on the bioactive compounds of strawberry leaves. The application of sorbitol at different concentrations (0, 25, 50 mM and 75 mM) greatly improved strawberry characteristics such as total chlorophyll, chlorophyll a and b, carotenoids, and total phenolics. As sorbitol concentrations increased, chlorophyll a and chlorophyll b values increased in the samples taken during the fruiting period and higher values were obtained. The carotenoid content increased by approximately 189.49% and the total phenolic content increased by 30.85% in strawberry plants treated with sorbitol compared with the control. Supply of sorbitol decreased flavonoid content. The results indicate that sorbitol treatment has no inhibitory influence on the overall growth of strawberries. Among the biochemical parameters analyzed, chlorophyll, phenolic, and carotenoid contents increased, whereas flavonoid content decreased with sorbitol application.